Arthroscopic Centralization Technique for Isolated Meniscotibial Ligament Insufficiency Leading to Medial Meniscal Extrusion: Knotless Anchor-Based Technique - Michele Malavolta, M.D.; Alessandro Carrozzo, M.D.; Silvio Mezzari, M.D. (Arthroscopy Techniques)
Medial meniscal extrusion, defined as a 3-mm external displacement of the meniscus, is often associated with ligamentous abnormalities and leads to loss of the stress distribution function of the meniscus. To restore meniscal position and function, meniscal centralization techniques have been developed. This study presents the pearls and pitfalls of an arthroscopic technique of medial meniscal centralization using a knotless soft anchor.